2022
DOI: 10.1088/1361-665x/ac9ba9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the reflow process on IMC growth for different devices and complex components

Abstract: Intermetallic compound (IMC), as an inevitable part between pad and solder, has a severe effect on the strength and reliability of microelectronic interconnection. Here, an investigation was carried out on IMC growth for different devices and complex components. The device-level experiments were conducted with five factors: peak temperature, time duration above solder liquidus temperature, the thickness of solder paste, surface finish types, and package types including BGA and QFP. Meanwhile, four complex comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The non-airtightness of the plastic seal causes the intrusion of a large number of nonpolar molecules and polar molecules along the micropores, including O2, which can undergo oxidation reactions, and H2O, which can undergo corrosion reactions [44,45. One of the well-established mechanisms in the research field is the oxidation of the copper substrate in the plasticized copper substrate or the RDL (ReDistribution Layer) in the presence of O2 and water molecules carrying Na + , Cl − , and other impurity ions through the chip passivation layer, and the metal-layer corrosion reaction [13][14][15][16][17][18][46][47][48], as shown in In 1972, Sharpe proposed the interphase concept to describe the transition regi the interface between two phases of different materials [50]. At the EMC/Cu inte when the oxide thickness of the Cu substrate is in the range of 20-30 nm, the increa surface roughness leads to the enhancement of the binding at the two-phase inte In 1972, Sharpe proposed the interphase concept to describe the transition region at the interface between two phases of different materials [50].…”
Section: Chemical Damage By Moisturementioning
confidence: 99%
See 2 more Smart Citations
“…The non-airtightness of the plastic seal causes the intrusion of a large number of nonpolar molecules and polar molecules along the micropores, including O2, which can undergo oxidation reactions, and H2O, which can undergo corrosion reactions [44,45. One of the well-established mechanisms in the research field is the oxidation of the copper substrate in the plasticized copper substrate or the RDL (ReDistribution Layer) in the presence of O2 and water molecules carrying Na + , Cl − , and other impurity ions through the chip passivation layer, and the metal-layer corrosion reaction [13][14][15][16][17][18][46][47][48], as shown in In 1972, Sharpe proposed the interphase concept to describe the transition regi the interface between two phases of different materials [50]. At the EMC/Cu inte when the oxide thickness of the Cu substrate is in the range of 20-30 nm, the increa surface roughness leads to the enhancement of the binding at the two-phase inte In 1972, Sharpe proposed the interphase concept to describe the transition region at the interface between two phases of different materials [50].…”
Section: Chemical Damage By Moisturementioning
confidence: 99%
“…Researchers’ studies on delamination mechanisms have mainly focused on thermal stress damage and moisture damage. Explaining the delamination phenomenon from the stress–strain perspective alone, it has been found that, at the delamination interface, mainly due to the interface between the two phases of the material, the plastic deformation of the two-phase material is formed under the action of the alternating shear stress, which ultimately leads to the failure of delamination [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. At the same time, under the intrusion of moisture, ionic contaminants corrode the chip, and moisture thermal expansion is also the main reason for the device to appear to suffer from the “popcorn” effect [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation